(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the quality of the oil and / or grease used in the frying process in SA. Methodology: This is a descriptive study, with a quantitative approach, based on the evaluation of frying oil in food services in the municipality of Santa Maria / RS. During the period from March to June 2019, on-site visits were carried out at the time of the frying procedures. A visual follow-up of this procedure was performed, a form was used to collect information and the saturation of the oil was verified through metering strips. The quantitative data were tabulated in Excel spreadsheet and analyzed using simple descriptive statistics. Results: More than 90% of the establishments conduct the daily frying process. The most used oil in this process is vegetable (96.3%). In 74.1% the oil and/or fat was restored when it was already reduced, also in 74.1% the frying process happened in a discontinuous way. In 81.5% there is no control of the temperature of the oil and/or fat during the frying process. Conclusion: Incorrectly use the oil and/or fat used in the frying process. This can lead to various health risks. It is important to emphasize the presence of nutrition professionals as a tool to promote best practices in this process, guaranteeing the population safe and nutritionally adequate food.